2020
DOI: 10.1155/2020/2098325
|View full text |Cite
|
Sign up to set email alerts
|

Bone Metastases Pattern in Newly Diagnosed Metastatic Nasopharyngeal Carcinoma: A Real-World Analysis in the SEER Database

Abstract: Objective. To evaluate the prevalence rate and survival situation of bone metastases in initial nasopharyngeal carcinoma (NPC) patients and the hazard and forecast elements of bone metastases NPC patients. Patients and Methods. The data collected from Surveillance, Epidemiology, and End Results (SEER) program between 2010 and 2016 were evaluated. Univariate and multivariable logistic analysis and the Cox regression were carried out to estimate predictors and elements of the being of bone metastases at diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 22 publications
(28 reference statements)
2
9
0
Order By: Relevance
“…A statistical analysis of multisite metastases showed that bone was the most common metastatic organ, which is consistent with findings from several other studies covering all age groups 22 26 . Because no previous epidemiological statistics for elderly people were found, we were unable to obtain the results of a large sample analysis to compare them with our results.…”
Section: Resultssupporting
confidence: 89%
“…A statistical analysis of multisite metastases showed that bone was the most common metastatic organ, which is consistent with findings from several other studies covering all age groups 22 26 . Because no previous epidemiological statistics for elderly people were found, we were unable to obtain the results of a large sample analysis to compare them with our results.…”
Section: Resultssupporting
confidence: 89%
“… 30 Studies have also shown strong associations between sex and race and bone metastasis in patients with nasopharyngeal carcinoma. 31 Other studies have shown that race does not predict bone metastasis in men with non-metastatic castrated prostate cancer. 32 Additional studies have shown that women have a lower risk of bone metastasis and good prognosis in non-sex-specific cancers.…”
Section: Discussionmentioning
confidence: 97%
“…Some preclinical studies have demonstrated the anti‐metastatic effects of TFP. The bones are the most common metastatic sites of NPC, and bone metastasis can impair the survival and quality of life of patients 38 . One study showed that TFP is a potential drug for treating bone metastasis of breast cancer by antagonizing dopamine receptor D2 39 .…”
Section: Discussionmentioning
confidence: 99%
“…The bones are the most common metastatic sites of NPC, and bone metastasis can impair the survival and quality of life of patients. 38 One study showed that TFP is a potential drug for treating bone metastasis of breast cancer by antagonizing dopamine receptor D2. 39 In our results, we also showed that NPC-BM cells were suppressed by TFP.…”
Section: Discussionmentioning
confidence: 99%